Strategi Dinas Kesehatan Kabupaten Sukoharjo Dalam Menekan Angka Kematian Ibu Di Masa Pandemi Covid-19 (Kajian Pada Program Semua Bumil Melahirkan Harus Selamat) - Amelia Christiani; Tiyas Nur Haryani (Jurnal Mahasiswa Wacana Publik, 2022)
This study aims to examine the strategy of the Sukoharjo Health Agency in suppressing MMR during the Covid-19 pandemic in the Semilir Hasmat Program. This research is descriptive qualitative research with interview and documentation data collection techniques. The purposive sampling technique used to determine the informants in this study. The analysis technique in this study used the data analysis technique of Miles and Huberman. The results of the study show that in suppressing MMR during the Covid-19 pandemic, the Sukoharjo Health Agency carried out 4 strategies in the Semilir Hasmat Program, including organizational strategy, program strategy, resource support strategy, and institutional strategy. Organizational strategy is carried out by creating a vision, mission, goals and objectives that are in harmony between the Sukoharjo Regency, the Sukoharjo Health Agency, and the Semilir Hasmat Program. Program strategy executed through examination activities by ob-gyn doctors, integrated ANC services, classes for pregnant women and mobile USG. The resource strategy is implemented by maximizing human, financial and infrastructure resources. Furthermore, the institutional strategy is carried out through strengthening cooperation between hospital and FTKP involving community cadres, and comparative studies.